A phase 1, randomized, placebo‐controlled, dose‐escalation study of an anti‐IL‐13 monoclonal antibody in healthy subjects and mild asthmatics. (14th December 2012) - Hodsman, Peter; Ashman, Claire; Cahn, Anthony; De Boever, Erika; Locantore, Nicholas; Serone, Adrian; Pouliquen, Isabelle
<x xml:space="preserve">Abstract</x> WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT IL‐13 can recapitulate the key pathological and clinical features of asthma. Exhaled NO (FeNO) concentrations are elevated under conditions of pulmonary inflammation, including asthma. Therapies that inhibit signalling by both IL‐13 and the functionally redundant cytokine IL‐4 have demonstrated reductions in FeNO, although relationship to dose was not reported. WHAT THIS STUDY ADDS This study provides the first report of the safety and pharmacokinetics of GSK679586, a novel humanized monoclonal antibody that prevents IL‐13 from binding its two known receptors. This is the first report of the effects on FeNO of a therapy targeting IL‐13 alone. Inhibition of IL‐13 signalling by GSK679586 produces dose‐ and time‐dependent reductions in FeNO in mild intermittent asthmatics. Thus, FeNO appears to be a dose‐ and time‐responsive clinical biomarker of IL‐13 inhibition in mild asthma. AIMS IL‐13 is implicated as an important mediator of the pathology of asthma. This first clinical study with GSK679586, a novel humanized anti‐IL‐13 IgG1 monoclonal antibody, evaluated the safety, pharmacokinetics and pharmacodynamics of escalating single and repeat doses of GSK679586. METHODS In this randomized, double‐blind study, healthy subjects received single intravenous infusions of GSK679586 (0.005, 0.05, 0.5, 2.5, 10 mg kg−1) or placebo and mild intermittent asthmatics received two once monthly intravenous infusions of GSK679586 (2.5, 10, 20 mg kg−1) or placebo. RESULTS GSK679586 displayed approximately linear pharmacokinetics (based on AUC and Cmax) with limited accumulation upon repeat administration. In mild intermittent asthmatics, treatment with GSK679586 produced an increase in serum total IL‐13 concentrations, indicative of GSK679586–IL‐13 complex formation. Additionally, mean levels of exhaled nitric oxide (FeNO), a marker of pulmonary inflammation, were reduced relative to baseline at 2.5, 10 and 20 mg kg−1 doses of GSK679586 at both 2 weeks (19%, 44% and 52% decreases) and 8 weeks (29%, 55% and 42% decreases) after the second infusion. GSK679586 was well tolerated; the incidence of AEs was comparable across all presumed biologically active doses and there were no treatment‐related SAEs. CONCLUSIONS GSK679586 demonstrated dose‐dependent pharmacological activity in the lungs of mild intermittent asthmatics. These findings, together with the favourable safety profile and advantageous PK characteristics of a monoclonal antibody (e.g. a long half‐life supporting less frequent dosing), warrant further investigation of GSK679586 in a broader asthma patient population.